Value of the 'clicky hip' in selective screening for developmental dysplasia of the hip. (June 2019) - Marson, B. A.; Hunter, J. B.; Price, K. R.
Abstract : Aims: The aim of this study was to review the value of accepting referrals for children with 'clicky hips' in a selective screening programme for hip dysplasia. Patients and Methods: A single-centre prospective database of all referrals to the hip clinic was examined to identify indication for referrals, diagnosis, and treatment. All patients referred received a standardized ultrasound scan and clinical examination by an orthopaedic consultant. Results: There were 5716 children referred to the orthopaedic hip clinic between 1 June 2014 and 26 September 2018. In all, 1754 children (30.1%) were referred due to 'clicky hip' with no additional risk factors or indications for ultrasound scan. A total of 123 children (7.1%) referred with 'clicky hip' and no additional risk factors or examination findings had an abnormal initial hip ultrasound, including 16 children (0.9%) with dysplastic hips. Of the 141 children who required treatment in a Pavlik harness during the study period, 23 (16%) had been referred with a 'clicky hip' and no additional risk factors or examination findings, including six children with Graf 3 or 4 hips. Conclusion: There is significant value in reviewing children with an isolated 'clicky hip'. Many children who require treatment are referred to the orthopaedic service as 'clicky hip' with no additional risk factors. In a pragmatic pathway with a diverse population of clinicians performing baby checks, 'clicky hip' is an important indication for referral and should not be discarded. Cite this article: Bone Joint J 2019;101-B:635–638.